A FORMALISM CRITIQUE OF DJOKO PEKIK'S PAINTINGS ENTITLED GO TO HELL CROCODILE - Arum Wilis Kartika Ayuningtari (JURNAL PAKARENA, 2022)
This research aims to explain the aesthetic aspects of Djoko Pekik's paintings entitled Go to Hell Crocodile. This research uses descriptive qualitative research methods. The approach step taken in this research is the art criticism approach with analytical interpretation using Feldman's formalism art criticism. The data was obtained through observation and literature studies. The subject of criticism in this research is a painting entitled Go to Hell Crocodile (2014) made by Djoko Pekik, a realist-expressive painter from Yogyakarta. To Feldman's critique structure, in this art criticism paper, there are four parts of explanations namely description, formal analysis, interpretation, and evaluation or decision. The research's results showed that there was a significant consistency in Djoko Pekik's paintings entitled Go to Hell Crocodile (2014) with his old work in 1998 entitled Berburu Celeng. This consistency is found in the concept of ideas, he brings up the phenomenon of Indonesian socio-politics issues. In addition, consistency is also found in visual concepts such as the selection of the main object's form, the supporting objects, and his unique expressive painting styles. The results of the observations also found some transformations in the visual aspects of Djoko Pekik's paintings, but some of these aspects did not change his style in a major way and this aspect could not even be known if the art enthusiast did not make in-depth observations.